Automated detection of photoreceptors in in-vivo retinal images (2016)
The inclusion of adaptive optics (AO) into ophthalmic imaging technology has allowed the study of histological elements of retina in-vivo, such as photoreceptors, retinal pigment epithelium (RPE) cells, retinal nerve fiber layer and ganglion cells. The high-resolution images obtained with ophthalmic AO imaging devices are rich with information that is difficult and/or tedious to quantify using manual methods. Thus, robust, automated analysis tools that can provide reproducible quantitative information about the tissue under examination are required. Automated algorithms have been developed to detect the position of individual photoreceptor cells and characterize the RPE mosaic. In this work, an algorithm is presented for the detection of photoreceptors. The algorithm has been tested in synthetic and real images acquired with an Adaptive Optics Scanning Laser Ophthalmoscope (AOSLO) and compared with the one developed by Li and Roorda. It is shown that both algorithms have similar performance on synthetic and cones-only images, but the one here proposed shows more accurate measurements when it is used for cones-rods detection in real images.